Optimalisasi Kesejahteraan Peserta Didik Dengan Menerapkan Prinsip-Prinsip Psikologis - Helmi Suardi, Sofyan Sufri, Desiana, Eka Warnidar, Eka Oktarina Riani (Bansigom Na Publisher, 2024)
Education plays a central role in shaping the well-being of students through the application of psychological principles. The research focuses on motivation, psychological needs, and behavioral patterns to enhance holistic well-being. An analysis of the well-being dimensions of students is expected to provide a comprehensive overview for the development of targeted intervention strategies. The Community Commitment Program in Central Aceh has become a real implementation, involving 253 lecturers, 60 heads of school, and students, with positive evaluations from stakeholders. This research affirms that understanding and implementation of psychological principles in education is key to creating a learning environment that supports the holistic growth of learners